Participatory Video on Rural Empowerment in Nicaragua - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Participatory Video project with la Fundacion Entre Mujeres (FEM) in Esteli, Nicaragua. After 8 days of hard work the girls created their own participatory video on rural empowerment of (young) women in Nicaragua. This project is conducted by CCAFS in collaboration with the International Centre for Tropical Agriculture (CIAT) and the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics) and is funded by Humidtropics.